2013
DOI: 10.1002/jgrb.50113
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence history, crustal structure, and evolution of the Somaliland‐Yemen conjugate margin

Abstract: [1] We have used biostratigraphic data from deep exploration wells to determine the tectonic subsidence history of the Somaliland (northwestern Somalia)-Yemen conjugate margin, a poorly known margin in the central part of the Gulf of Aden. Bathymetry and magnetic anomaly data suggest the Gulf of Aden is a young feature that formed following the rifting apart and breakup of the African and Arabian plates~32 Ma. Our tectonic subsidence data suggest, however, that the present-day Gulf of Aden developed on an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 77 publications
3
41
0
Order By: Relevance
“…In this case, the calculated tectonic subsidence of ~1800 m during the fast rifting of pristine lithosphere dramatically reduces to <500 m when the same rifting event occurs on previously rifted lithosphere, independent of the previous boundary velocity. Albeit general, these results are in agreement with Ali and Watts [], Cunha [], and Chen [] who used multiple event subsidence models to show the effect of rifting history in specific geological cases such as the Gulf of Aden [ Ali and Watts , ], Iberian margin [ Cunha , ] and Baiyun Sag in the South China Sea [ Chen , ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this case, the calculated tectonic subsidence of ~1800 m during the fast rifting of pristine lithosphere dramatically reduces to <500 m when the same rifting event occurs on previously rifted lithosphere, independent of the previous boundary velocity. Albeit general, these results are in agreement with Ali and Watts [], Cunha [], and Chen [] who used multiple event subsidence models to show the effect of rifting history in specific geological cases such as the Gulf of Aden [ Ali and Watts , ], Iberian margin [ Cunha , ] and Baiyun Sag in the South China Sea [ Chen , ].…”
Section: Discussionsupporting
confidence: 87%
“…Chen [] used a rifting‐cooling‐rifting cycle to model the subsidence in the Baiyun Sag along the continental slope of the South China Sea. A similar modeling strategy was adopted by Ali and Watts [] and Cunha [] to interpret the subsidence history of the Gulf of Aden and the Iberia margin, respectively. Armitage et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligocene-Miocene rifting of the Gulf of Aden subjected the conjugate margins of Somaliland (NW Somalia) and southern Yemen to an extensional system of east-west to ENE-WSW striking normal faults which reactivated pre-existing Mesozoic faults (Ali and Watts, 2013;Bellahsen et al, 2013;Leroy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The basin contains both Upper Jurassic source rocks and a variety of reservoir rocks. Furthermore, by backstripping biostratigraphic data from exploration wells Ali and Watts (2013) and Ali and Watts (2016) showed that basins in northern Somalia have undergone three main rift phases with intervening periods of uplift and erosion. Initial phases of rifting occurred in the Late Jurassic and Late Cretaceous as a result of the late-stage break-up of Gondwana and a rapid increase in the spreading rate on the ridges separating the African and Indian plates respectively (Ali and Watts, 2016).…”
Section: Introductionmentioning
confidence: 99%